ALTERNATIVE MODEL CONCEPT OF LAW TO RESPOND THE IMPACT OF GLOBALIZATION OF LIBERAL DEMOCRATION IN INDONESIA - Amarini, Indriati (Faculty of Law, Universitas Jenderal Soedirman, 2015)
Democracy is a universal state order with the concept of sovereignty vested in the people and implemented as an application of human dignity with the value of brotherhood, equality and freedom. The big issue for Indonesia is a communal atmosphere and collective behavior that is fading while the competitive behavior of individuals is increasingly valued. Subsequent impact is the blurring of the benchmark assessment of individual behavior, which in turn trigger the formation of social issues that increasingly complex. There are at least three alternative models of law concept responded impact of globalization of democracy, first: engineering and social control over management model, characterized by results rather than process-oriented; second, the critical model where the law continually refined through process of falsification; third, the law is formulated, implemented and enforced based on the postulate–progressiveresponsive.Keywords: globalization, democracy, law concept